Arsenic Contamination in Groundwater of Punjab - An Overview - Kaur, Prabhdeep; Singh, Inderpreet; Kaur, Paramjeet (IJRDO-Journal of Applied Science, 2015)
Groundwater is a common pool resource for drinking and irrigation purposes in Punjab and can be drawn on demand wherever and whenever needed. Pollution by various toxic chemicals is posing a great problem nowadays and contamination of arsenic in groundwater is estimated to affect various parts of the country especially near the gangetic fluvial plains of India including Punjab. As is found to be carcinogenic, As(III) is more toxic than As(IV). In this study, overview of the contamination of arsenic in groundwater of Punjab is studied. It is found that a number of areas have been affected with As contamination that exceeds the standard given in BIS(2012). Being an agricultural state it becomes even more important to identify and curb the problem of As contamination in Punjab.